The Integration of Psychology and Qur’anic Spirituality in Self-Concept: Implications of Hamka's Tafsir Al-Azhar Analysis: (Integrasi Psikologi dan Spiritualitas Al-Qur'an dalam Konsep Diri: Implikasi Analisis Tafsir Al-Azhar Hamka) - Nurcahyati Nurcahyati; Zakaria Husin Lubis; Hafid Nur Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2026)
This study aims to examine the formation of self-concept according to Hamka in Tafsir Al-Azhar and its implications for Islamic psychology. Using a literature analysis approach and Hasan Hanafi's maudhu'i interpretation, this study explores the integration of Qur'anic values in the formation of a healthy self-concept, covering psychological, moral, and spiritual dimensions. The main focus is to analyze how Hamka relates self-concept to spirituality, desire control, and the application of moral values in the Qur'an. This study also connects Hamka's thoughts with modern psychological theories, such as self-actualization and self-regulation, to address issues of identity and mental health in modern society. The results of the study show that Hamka's concept of self is based on purification of the soul (tazkiyatun al-nafs), which is the foundation for forming a healthy concept of self that is capable of facing psychological and social challenges. The implication is that the integration of spirituality and morality in the formation of self-concept provides a holistic approach to overcoming mental health and identity crises. This study offers a new perspective in the development of Islamic psychology by incorporating spirituality in the formation of a positive self-concept, as well as opening up further research potential for practical applications in mental health, character education, and community development.